Pollution by heavy metals in the Moche River Basin, 1980 - 2010, La Libertad - Peru - Huaranga Moreno, Félix (2012)
The pollution of the continental waters is a problem at a world scale, mainly due to the impact of the mining tailings. Using top technologies as neutralization plants of acid waters, many companies are mitigating the impact of this functioning; so taking as a reference the changes in the concentration of heavy metals present in water, soils and cultivations of the high, middle and low basin of the Moche river, samplings of water were obtained at eight stations of the Moche river (Trujillo, Peru), and in four sectors of its margins for soils and cultivations. The most representative heavy metals in water were found in the high basin during the year 1980: iron (557.500 ppm), lead (100.375 ppm), cadmium (4.550 ppm), copper (6.900 ppm), zinc (262.900 ppm) and arsenic (9.000 ppm); whereas in the soils the higher concentrations were found on the right margin of median basin in the year 1980: iron (83.400 mg/kg); lead (0.820 mg/kg); cadmium (0.012 mg/kg); copper (1.240 mg/kg); zinc (0.380 mg/kg) and arsenic (0.016 mg/kg); in relation to the metal accumulation in the cultivations, iron (0.6525 mg/kg) was predominant, being the yucca (Manihot esculentus) the most contaminated cultivation. It is concluded that, most contamination level of water analysis was present in the high basin during 1980, whereas the right side of the median basin highest levels of contamination in the samples of soils; relating to the cultives, the yucca (Manihot esculentus) was the species most contaminated.